International Cycling Conference 2017. Bridging the gap between research and practice 19-21 September 2017, Mannheim, Germany. Conference Proceedings. - (:unkn) unknown (Umweltbundesamt (UBA), 2019)
Die International Cycling Conference (ICC) 2017 war eine interdisziplinäre und internationale Konferenz des Umweltbundesamtes (UBA), zusammen veranstaltet mit PASTA (Physical Activity through Sustainable Transport Approaches) und THE PEP (Transport, Health and Environment Pan-European Programme) sowie der Stadt Mannheim, der European Cyclists' Federation (ECF), dem Deutschen Institut für Urbanistik (Difu) und der Deutschen Gesellschaft für Internationale Zusammenarbeit (GIZ) , in der die die Rolle der aktiven Mobilität aus internationaler Perspektive herausgestellt wurde. Im Mittelpunkt der Veranstaltung standen Synergien in den Bereichen Verkehrsplanung, Gesundheitsfürsorge, Umweltqualität, wirtschaftliche Entwicklung sowie soziale Fragen und vor allem Wissens- und Erfahrungsaustausch zwischen Forschung und Praxis. Der Band dokumentiert die Tagungsbeiträge größtenteils in Form von Abstracts. Vier "Selected Papers" sind mit ihrem vollen Text enthalten: Promoting childrens' cycling through cycling courses in city traffic. S. 112 ff; Can public bike sharing systems encourage migrant women to use bicycles? S. 122 ff; Promoting active travel for all in European urban regions - a review of evaluated initiatives. S. 137 ff; Transport poverty and urban cycling: a case study Rotterdam. S. 156 ff.

The Conference Proceedings are the final report of the International Cycling Conference (ICC) which took place from 19 until 21 September 2017 in Mannheim, Germany. Marking the 200th birthday of the bicycle this interdisciplinary and international three-day conference by the German Environment Agency emphasized the importance of cycling from an international perspective. 292 participants, 90 presenters and nearly 50 poster presentations focussed on the synergies between transport planning, health care, environmental quality, economic and business development as well as social issues and above all the exchange of knowledge and experience between research and practice. The audience of the conference and also this publication are researchers, practitioners, political representatives at all levels, NGOs, transport planners, specialist doctors for public health, designers, architects and engineers.
Keywords: Fahrradförderung; Stadtverkehr; Fahrradverkehr; Verkehrsplanung; Fahrradinfrastruktur; Mobilität; Umweltqualität; Gesundheitsförderung; International